2023
DOI: 10.37934/arfmts.103.2.141156
|View full text |Cite
|
Sign up to set email alerts
|

Power Optimization of The Horizontal Axis Wind Turbine Capacity of 1 MW on Various Parameters of The Airfoil, an Angle of Attack, and a Pitch Angle

Abstract: The rotor is one of the vital components of a wind turbine. In the design of the rotor, the expected result is the most optimal power. This purpose study is to optimization of the Horizontal Axis Wind Turbine power of various parameters such as airfoil, angle of attack, and pitch angle. Airfoils (NACA 4412-2412 T.E. mod, NACA 2412-4412 T.E. mod, NACA 4412-2412 L.E. mod, NACA 2412-4412 L.E. mod), angle of attack (0, 2, 4, 6), and pitch angle (0, 1, 2, 3) are the parameter variations used. The simulation method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Their results revealed that (1) the turbine exhibited C P,max at a blade pitch angle of 0 • , (2) the starting process of the turbine was characterized by a long idling period, and (3) the turbine's startup was best for a blade pitch angle of 20 • . Kriswanto et al [23] adopted the Taguchi method to optimize the performance of a HAWT. Their analysis of variance (ANOVA) results indicated that of all the investigated parameters, the airfoil had the strongest influence on the rotor power of the HAWT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results revealed that (1) the turbine exhibited C P,max at a blade pitch angle of 0 • , (2) the starting process of the turbine was characterized by a long idling period, and (3) the turbine's startup was best for a blade pitch angle of 20 • . Kriswanto et al [23] adopted the Taguchi method to optimize the performance of a HAWT. Their analysis of variance (ANOVA) results indicated that of all the investigated parameters, the airfoil had the strongest influence on the rotor power of the HAWT.…”
Section: Introductionmentioning
confidence: 99%
“…Additional information on this method is provided in the papers of Roy [33] and Ross [34]. Some studies have adopted the Taguchi method to optimize wind turbine design [23,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Orthogonal Array (OA) is one of the major advantages of the Taguchi method. Taguchi method also helps in minimizing the number of experiments required in optimization purpose [6][7][8][9][10][11]. The important characteristics of HTL is high conductivity, high transparency, favorable process solution and stability, high WF and good hole mobility [12].…”
Section: Introductionmentioning
confidence: 99%